Efektivitas Undang-Undang Perampasan Aset pada Pelaku Tindak Pidana Pencucian Uang Berdasarkan Hukum Pidana - Sayib Fauzi Adiansyah; Mohammad Irfandianto; Dominikus Rato; Fendi Setyawan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Money laundering is an action to eliminate the source of money resulting from criminal acts which is later found to have been generated legally. Money laundering is a crime that is difficult to crack. Therefore, the application of legal sanctions against perpetrators must be balanced with criminal sanctions and confiscation of assets against perpetrators. This research uses a normative research type with a legal and conceptual approach. The crime of money laundering is a crime that needs attention because it is often associated with losses to the state and society, therefore legal action is needed to deter the perpetrators, but the obstacle that occurs is the punishment in Article 2 of the Assets Bill which only applies confiscation of assets resulting from crime without any punishment of criminals. This is not in accordance with the function of law. So the results and conclusions can be drawn that not implementing punishment against the perpetrator will most likely not have a deterrent effect, therefore it should be important to implement punishment and confiscation of assets because both must be implemented simultaneously as a form of firm state action to provide a deterrent effect.